Вы находитесь на странице: 1из 3

# SUMMARY OF 2

ND
ORDER ORDINARY DIFFERETIAL EQUATION

1. Homogeneous ODE (Ordinary Differential Equation)
1.1 Second Order ODE with Constant Coefficients
General form of ODE:
d
2

dx
2
+o
d
dx
+ by = u (o, b = constants)

Solution Basis: y = c
xx

Characteristic Equation: y
0
1;
d
dx
z;
d
2

dx
2

2
z
2

z
2
+ oz +b = u

1.2 Second Order Euler-Cauchy (Equi-dimenssional)
General Form of PDE: x
2
d
2

dx
2
+ ox
d
dx
+by = u

Solution Basis: y = x
m

Auxiliary Equation: m
2
+(o 1)m +b = u

Case Roots of Auxiliary Eqn Basis of Solution General Solution
I
Distinct real
m
1
, m
2

x
m
1
, x
m
2
y = c
1
x
m
1
+c
2
x
m
2

II
Real double root
m =
1
2
(1 o)
x
m
, (lnx) x
m
y = (c
1
+c
2
lnx)x
m
; m =
1 o
2

III
Complex conjugate
m
1,2
=
1
2
(1 o) _i4b
x
1-u
2
cos(4blnx)
x
1-u
2
sin(4blnx)
y = x
1-u
2
|A cos(4b lnx)
+B sin(4b lnx)|
2. Non-Homogeneous ODE
General Form of ODE:
d
2

dx
2
+p(x)
d
dx
+ q(x)y = r(x)

General Form of Solution: y = y
h
+y
p

y
p
is determined by using its approriate method(s).

If p(x) and q(x) are constants, then the non-homogeneous ODE can be solved by using both the
Method of Undetermined Coefficients or the Method of Variation of Parameters (Lagranges
Method).

If p(x) and q(x) are NOT constants, then the non-homogeneous ODE has to be solved by using the
Method of Variation of Parameters.

2.1 Method of Undetermined Coefficients (For Contant Coefficients only)
The particular solution y
p
is determined by using Table 2.1.

2.2 Method of Variation of Parameters (Lagranges Method)
The particular solution y
p
is assumed in the following form:
y
p
= u(x). y
1
(x) +:(x). y
2
(x) (a)
with y
1
and y
2
are solutions of the homogeneous ODE.

First derivatives of (a) with respect to x is y
p
i
= u
i
. y
1
+:
i
. y
2
+u. y
1
i
+:. y
2

Lets set u
i
. y
1
+:
i
. y
2
= u (b)
so that y
p
i
= +u. y
1
i
+:. y
2

y
p
ii
= u
i
. y
1
+:
i
. y
2
+u. y
1
+:. y
2

Substituting y
p
, y
p
i
, anu y
p
into the non-homogeneous ODE gives

u|y
1
ii
+p(x)y
1
i
+q(x)y
1
] +:|y
2
ii
+p(x)y
2
i
+q(x)y
2
] + u
i
. y
1
i
+:
i
. y
2
i
= r(x)

i
. y
1
i
+:
i
. y
2
i
= r(x) (c)

Eqn (b) and (c) give u and :, which can be integrated to obtain u(x) and :(x) as

dx
y y y y
x r y
x u

=
1 2 2 1
2
) (
) ( and dx
y y y y
x r y
x v

=
1 2 2 1
1
) (
) (

Note:
For further and complete explanation on this matter, students are suggested to read Chapter 2 of
Advanced Engineering Mathematics, Erwin Kreyszig, Ed.9 text book and/or other related materials in
literatures or on websites.